A dictionary of genetic engineering - Oliver, Stephen G.; Ward, John M. (Cambridge Univ. Press, 1985)
Over 500 terms defined; intended as technical terminology and slang or jargon also used in the field. Will interest workers and students in cell biology, developmental biology, genetics, chemical engineering, as well as those in commerce and politics with a concern for the new technology. Contains illustrations. Miscellaneous appendixes.
Keywords: Génie génétique - Dictionnaires anglais; Genetic Engineering -- Dictionary -- English; Genetic engineering -- Dictionaries; Englisch; Wörterbuch; Gentechnologie